2021
DOI: 10.1016/j.cej.2020.127522
|View full text |Cite
|
Sign up to set email alerts
|

Where do we stand to oversee the coronaviruses in aqueous and aerosol environment? Characteristics of transmission and possible curb strategies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 174 publications
(228 reference statements)
0
16
0
2
Order By: Relevance
“…Sludge digestion or stabilization process by combining both thermal hydrolyses with a moderate temperature range of 35 to 40 °C and long residence time of 10 to 20 days that are commonly used in large treatment plants has been reported to effectively inactivate the SARS-CoV-2 load during the wastewater treatment process ( Balboa et al, 2021 ). It was also suggested that heating treatments using ultra-temperature aerobic fermentation, thermophilic anaerobic digestion, and sludge incineration could effectively inactivate the SARS-CoV-2 and other forms of coronaviruses ( Ji et al, 2020 ). However, a previous study indicated that mesophilic anaerobic digestion could not effectively inactivate pathogens in the sewage sludge ( Viau et al, 2011 ).…”
Section: Challenges Associated With Virus Inactivation and Removal In...mentioning
confidence: 99%
“…Sludge digestion or stabilization process by combining both thermal hydrolyses with a moderate temperature range of 35 to 40 °C and long residence time of 10 to 20 days that are commonly used in large treatment plants has been reported to effectively inactivate the SARS-CoV-2 load during the wastewater treatment process ( Balboa et al, 2021 ). It was also suggested that heating treatments using ultra-temperature aerobic fermentation, thermophilic anaerobic digestion, and sludge incineration could effectively inactivate the SARS-CoV-2 and other forms of coronaviruses ( Ji et al, 2020 ). However, a previous study indicated that mesophilic anaerobic digestion could not effectively inactivate pathogens in the sewage sludge ( Viau et al, 2011 ).…”
Section: Challenges Associated With Virus Inactivation and Removal In...mentioning
confidence: 99%
“…In conventional wastewater treatment processes, the primary treatment (screens, grit chamber, primary clarifier) at WWTPs may not be effective because of the size of the coronavirus (60 to 220 nm), whereas the activated sludge flocs adsorption and membrane filtration could effectively remove coronaviruses from the aqueous phase [29] , [64] . However, the inactivation process is highly dependent on tertiary treatment with chemical oxidation disinfection and/or UV treatment [6] . Comparing the concentration of SARS-CoV-2 RNA in wastewater before and after treatment suggests that 1–2 log 10 viral titers can be removed [65] , depending on the process and operational conditions.…”
Section: State Of the Knowledge And Research Needsmentioning
confidence: 99%
“…There has been consensus on the role of water, sanitation and personal hygiene in reducing SARS-CoV-2 transmission and supporting the response to COVID-19 [2] , [3] , [4] . On the other hand, scientific reports indicated that SARS-CoV-2 has been widely detected in wastewater [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . The occurrence, fates and potential treatment approaches of this virus in the water cycle should be urgently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Пандемія коронавірусу COVID-19 стала серйозним викликом для сучасної медицини. Серед засобів запобігання інфікуванню найдоступнішими у використанні є маски, респіратори, захисні окуляри, щитки [2,4,5]. Але, на жаль, застосування вищевказаних засобів не забезпечує повний захист від інфікування, адже кожен п'ятий інфікований коронавірусом в Україні є медичним працівником [6].…”
unclassified
“…Але, на жаль, застосування вищевказаних засобів не забезпечує повний захист від інфікування, адже кожен п'ятий інфікований коронавірусом в Україні є медичним працівником [6]. Наведене обумовлює потребу в розробці нових методів індивідуального захисту органів дихання, які б одночасно вдовольняли критерії надійності, доступності та ергономічності [1,4].…”
unclassified